Insight Into Rho Kinase Isoforms in Obesity and Energy Homeostasis - Wei, Lei; Shi, Jianjian (Frontiers in Endocrinology, 2022)
Obesity and associated complications increasingly jeopardize global health and contribute to the rapidly rising prevalence of type 2 diabetes mellitus and obesity-related diseases. Developing novel methods for the prevention and treatment of excess body adipose tissue expansion can make a significant contribution to public health. Rho kinase is a Rho-associated coiled-coil-containing protein kinase (Rho kinase or ROCK). The ROCK family including ROCK1 and ROCK2 has recently emerged as a potential therapeutic target for the treatment of metabolic disorders. Up-regulated ROCK activity has been involved in the pathogenesis of all aspects of metabolic syndrome including obesity, insulin resistance, dyslipidemia and hypertension. The RhoA/ROCK-mediated actin cytoskeleton dynamics have been implicated in both white and beige adipogenesis. Studies using ROCK pan-inhibitors in animal models of obesity, diabetes, and associated complications have demonstrated beneficial outcomes. Studies via genetically modified animal models further established isoform-specific roles of ROCK in the pathogenesis of metabolic disorders including obesity. However, most reported studies have been focused on ROCK1 activity during the past decade. Due to the progress in developing ROCK2-selective inhibitors in recent years, a growing body of evidence indicates more attention should be devoted towards understanding ROCK2 isoform function in metabolism. Hence, studying individual ROCK isoforms to reveal their specific roles and principal mechanisms in white and beige adipogenesis, insulin sensitivity, energy balancing regulation, and obesity development will facilitate significant breakthroughs for systemic treatment with isoform-selective inhibitors. In this review, we give an overview of ROCK functions in the pathogenesis of obesity and insulin resistance with a particular focus on the current understanding of ROCK isoform signaling in white and beige adipogenesis, obesity and thermogenesis in adipose tissue and other major metabolic organs involved in energy homeostasis regulation.